Quality of Human Capital and Total Factor Productivity in New European Union Members States - Michal Bernard Pietrzak; Adam P. Balcerzak (Institute of Economic Research (IER), 2016)
Closing development gap and avoiding middle income trap are currently considered as the main challenges for the new EU member states. To obtain both those aims the countries must implement policies that support total factor productivity (TFP) growth. The main scientific purpose of the article is to examine the influence of quality of human capital (QHC) on TFP in Central European countries in the years 2000-2010. All the EU countries must be able compete internationally in reality of global knowledge economy. Thus, the QHC was analysed from the perspective of the knowledge-based economy. As the QHC is a multidimensional phenomenon in order to measure it and obtain time series for further econometric research, TOPSIS method was applied. To evaluate TFP the parameters of the Cobb-Douglas production function for the new EU members were estimated. Finally, it was possible to identify the relationship between the QHC and the level of TFP with application of dynamic panel model. The analysis was conducted for the years 2000-2010 based on Eurostat data. It confirmed a significant influence of the QHC on the level of TFP in the new EU members states.
Keywords: C23; C38; O47; 330; multiple-criteria decision analysis (MCDA); TOPSIS method; panel model; TFP; human capital; new EU members